The effect of a paced auditory serial addition test (PASAT) intervention on the profile of volatile organic compounds in human breath: a pilot study - Matthew A. Turner; Stephan Bandelow; Louisa Edwards; Pareen Patel; Helen J. Martin; Ian D. Wilson; Paul Thomas (2013)
This study sought to identify if detectable changes in human breath profiles may be observed following a psychological intervention designed to induce stress, a paced auditory serial addition test (PASAT). Breath samples were collected from 22 participants (10 male and 12 female) following a double cross-over randomized design with two experimental interventions. One intervention required participants to listen to classical music chosen to be neutral. The other intervention required participants to undertake a PASAT that induced cardiovascular responses consistent with acute stress. Both interventions also involved two sequences of cognitive function tests. Blood-pressure and heart-rate were recorded throughout each intervention and distal breath samples were collected onto Tenax® TA/Carbograph 1 thermal desorption tubes, using an adaptive breath sampler. Samples were collected before and after the PASAT. Breath samples were analysed by thermal desorption gas chromatography-mass spectrometry. Data registration using retention indexing and peak deconvolution followed by partial least-squares discriminant analysis identified six stress sensitive compounds. A principal components analysis model based on these components generated a model that predicted post-PASAT versus post-neutral intervention samples with a sensitivity of 83.3% and a selectivity of 91.6% for females, compared to 100% sensitivity and 90% selectivity for males. Of the six compounds indole, 2-hydroxy-1-phenylethanone, benzaldehyde, and 2-ethylhexan-1-ol were identified on the basis of mass spectral, retention indexing and confirmation against pure standards. 2-methylpentadecane was tentatively identified from mass spectral and retention indexing, whilst one component has yet to be assigned, although the mass spectrum is indicative of a terpene. Indole and 2-methylpentadecane concentrations increased in response to the PASAT intervention, while the other compounds reduced in their abundance in human breath, possibly as a result of ventilation effects.